Senkaku or Diaoyu Islands: the geopolitical interests of two states in tension (2013)
The border dispute between Japan and China over the Diaoyu or Senkaku Islands has been present for over forty years. This conflict is characterized by being cyclical, because for several years you can stop talking about the matter, and from one moment to another, actions by one of the two countries generate immediate discontent in the other, which ranges from simple street protests to Xenophobia and threats of commercial limitation. In order to better understand the situation, this article presents the most important historical facts throughout the dispute, as well as analyzes the actions taken by both parties in recent months.